PENDIDIKAN DASAR SEBAGAI PERINTIS TERDEPAN DALAM PENGUATAN KARAKTER MUSLIM - Fadillah, Ahmad Arif; Rafida, Aura Rahmatun; Wulandari, Cahya; Yuliawati, Dea; Ningrum, Dwi Rahayu Kusuma; Aen, Kurotul; Sahrurosi, Putri Adinda; Maulidya, Sarah; Wahdania; Nurzahro, Yufaida; Aulya, Zahra (Transpublika Publisher, 2022)
Basic Education as a leading pioneer in Strengthening Muslim Character has a relationship with character education. The implementation of Strengthening Character Education is carried out with the principle of school-based management which is the responsibility of school principals and teachers, as the fulfillment of the workload of teachers and school principals (Article 6 paragraph 3,4,5 PP 87/2017). According to President Joko Widodo's directive, character education at the basic education level gets a larger portion than education that teaches knowledge, for Elementary Schools by 70% while for Junior High Schools by 60%. The point of this research is management of strengthening characters education in elementary schools are includes planning, implementation and evaluation. The research method is descriptive qualitative through observation, documentation and interview.The result of this research obtained depiction that the first,the reinforcement of character education students have been implemented well through the preparation of goals, strategy and policy mapping and procedure mapping and program improvement using RPP and syllabus design; second, the implementation of character education runs well through activities of religious activities, nationalism cultivation, social care and environmental awareness; third, evaluation of the strengthening of character education management students through supervision activities on the implementation of activities by carrying out reflections, analysis and follow-up plans.